2019
DOI: 10.20965/jdr.2019.p0235
|View full text |Cite
|
Sign up to set email alerts
|

Development of Multi-Parameter Phased Array Weather Radar (MP-PAWR) and Early Detection of Torrential Rainfall and Tornado Risk

Abstract: This paper is an overview of a project concerned with “Early warning for torrential rainfall/tornado” under “Enhancement of Societal Resiliency against Natural Disasters,” which is one of eleven themes of the SIP (Cross-ministerial Strategic Innovation Promotion Program under the Council for Science, Technology and Innovation, the Cabinet Office, Government of Japan). The characteristics of the project are the development of a multi-parameter phased array weather radar (MP-PAWR) that enables the accomplishment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The major observation parameters of the MP-PAWR are the radar reflectivity factor (Z), Doppler velocity, differential reflectivity (ZDR), differential phase shift between horizontal and vertical polarization (ϕDP), and the correlation coefficient between the horizontal and vertical polarization (ρhv). Takahashi et al [7] detailed the specifications and performance of the MP-PAWR, and they found that the minimum sensitivity of the radar to be approximately 12 dBZ at a range of 30 km. Regarding the calibration of ZDR, a simple calibration using zenith observations was found to be insufficient.…”
Section: Observation and Analysis Methods Of Mp-pawr Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The major observation parameters of the MP-PAWR are the radar reflectivity factor (Z), Doppler velocity, differential reflectivity (ZDR), differential phase shift between horizontal and vertical polarization (ϕDP), and the correlation coefficient between the horizontal and vertical polarization (ρhv). Takahashi et al [7] detailed the specifications and performance of the MP-PAWR, and they found that the minimum sensitivity of the radar to be approximately 12 dBZ at a range of 30 km. Regarding the calibration of ZDR, a simple calibration using zenith observations was found to be insufficient.…”
Section: Observation and Analysis Methods Of Mp-pawr Datamentioning
confidence: 99%
“…In recent years, phased array weather radar technology has been developed [1][2][3][4][5]. The dualpolarization radar is one of several radars that have been developed using phased array weather radar technology [6,7]. The main characteristic of a phased array weather radar is that one-dimensional or two-dimensional electrical scanning can be conducted using a one-dimensional or two-dimensional phased array antenna.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reproduce realistic situations, we used localized torrential rain events recorded by MP-PAWR weather radar [11]. From the radar precipitation maps, we created three traffic risk maps in which the driving environment deterioration was indexed from 0 to 10 ( Figure 4) using "Class of rain and wind.…”
Section: Stimulimentioning
confidence: 99%
“…While localized short-term heavy rain is difficult to predict [10], its narrow coverage makes it possible to avoid through altered travel routes. The Japanese National Institute of Information and Communications Technology (NICT) is developing a weather radar system intended for the early detection and prediction of localized torrential rain [11], while also developing a cross-data collaboration platform [12] to optimize navigation by collecting information related to traffic risks such as various IoT sensor data including those from weather radar (Figure 1). This approach may allow localized torrential rain to be treated as a traffic risk and provide route guidance for avoidance.…”
Section: Introductionmentioning
confidence: 99%